Incidencia de herramientas pedagógicas digitales implementadas por docentes de básica primaria y secundaria para fortalecer el proceso de escritura (Memorias Sifored - Encuentros Educación UAN, 2022)
In today's society, digital writing has become very important because it is one of the tools that to cognitive development and interpersonal relationships. In this study, a qualitative methodology was used through contributes the document review method at the national and international levels. The objective is to identify the incidence and effects generated by ICT in elementary school and high school students, when using digital tools in scriptural processes. From a total of 50 references identified, 20 studies were selected under the criteria that were research published from the year 2017 and would account for the effects of ICT in the production of written texts. The selected texts -researches and theses- were examined and analyzed using an analysis matrix, in which the objectives, the population under study, the methodologies, the theoretical frameworks and the main findings derived from the results in these documents were investigated. The work’s results indicate that ICT can contribute significantly to the teaching and learning processes of writing; nevertheless, a high percentage of teachers only make use of ICT to transmit information.
Keywords: Multimodal writing; Technologies of the information and the communications (ICT); assessments; teaching tools; digital age